Accelerated aging and controlled deterioration for the determination of the physiological potential of onion seeds (Scientia Agricola, 2003)
International research on vegetable seed vigor is not at the same level attained for grain crops species. This study was conducted to identify reliable procedures for the accelerated aging and controlled deterioration tests to rank onion (Allium cepa L.) seed lots according to their physiological potential. Six seed lots of the cultivars Aurora and Petroline were evaluated in the laboratory for germination, first count, seedling vigor classification, traditional and saturated salt accelerated aging (41ºC / 48 and 72 h), controlled deterioration (24% of water / 45ºC / 24 h) and seedling emergence tests. Seed moisture content after the saturated salt accelerated aging test was lower and uniform, which is considered an important advantage in comparison to the traditional procedure. The saturated salt accelerated aging (41ºC / 48 and 72 h) and controlled deterioration (moisture content adjusted to 24% / 45ºC / 24 h) tests were the best procedures to assess the physiological potential of onion seeds, and are indicated for use in quality control programs.